The processing of agreement patterns in Croatian - Palmović, Marijan (Array, 2009)
Croatian is a language with agrement in the categories of person, case, gender and number. The verb agrees with its subject in person and adjectives and pronouns agree with the head nouns in gender, number and case within the NP. Although person agreement is treated as parallel to gender and number agreement in current linguistic theory, and case agreement is sometimes treated as exceptional, there are strong theoretical and typological reasons against such a view: first, treating person agrement in the same manner as case/gender/number agreement obscures the referential status of personal affixes in Head Marking languages, and secondly, peson agreement is much more common cross-linguistically. This paper presents the results of an ERP experiment which aimed to show the differences in processing errors in person agreement and, on the one hand, errors in case/gender agreement on the other hand.